Gerakan Karismatik dalam Gereja Katolik dan Protestan: sebuah perspektif kompatarif - adison adrianus sihombing (Penamas, 2019)
The pentecostalism movement experienced a rapid development which gave birth to several sectarian movements, due to a number of internal and external factors. This article illustrates and analyzes the development of ideas and the Charismatic Pentecostalism movement. In detail, the article tries to focus on: (a) how the history of the Pentecostalism movement in the world in general and in Indonesia in particular, (b) what is the Pentecostalism movement in the Catholic and Protestant Churches, (c) what are the doctrinal differences in the Charismatic movement in the Catholic and Protestant Churches? and (d) The extent of the influence of Catholic and Protestant Charismatics in Indonesia. Research using this approachmixed-methodconcludes a number of findings, including (i) the Pentecostalism Movement in Indonesia gave birth to the Charismatic movement in the Catholic Church and the Protestant Church, (ii) there are significant differences between Catholic and Protestant Charismatic doctrines, among them in matters of worship (ritual system) and ways of evangelism, and (iii) Catholic charismatics tend to develop in urban areas, while Protestant Charismatics are widespread, both in urban and rural areas.